SELECTED HEALTH BEHAVIOURS OF NURSES - Chuchra, Maria; Gorbaniuk, Julia (PSYCHOLOGICAL JOURNAL, 2019)
Currently, the role of nurses in healthcare is growing. Each day more demanding and responsible, practical tasks are put in front of them. They also have a leading role in the field of health promotion and professional knowledge about a healthy lifestyle. Due to their medical knowledge, they are expected to have a conscious, rational and critical attitude towards shaping and observing pro-health behaviours in their lives. The aim of this study is to compare the selected health behaviours of nurses. The research included 100 nurses and 100 women doing other professions. The respondents were tested with the matched pair-selection method, taking into consideration two variables: place of residence and age. The survey questionnaire was used. The nurses show similarities with respect to some health behaviours and show significant differences in the consumption of alcoholic beverages (the amount and kind) or regularity of preventive checks in comparison to others. The profession of nurses due to its’ specificity and requirement of constant care for ill person results in a very high level of stress. Nurses feel permanent pressure, which entails permission to use stimulants such as coffee, alcohol and to a lesser extent - smoking. Their role as promoters of a healthy lifestyle means that they try to take care of health through control or preventive examinations.